2005
DOI: 10.1111/j.1479-8301.2005.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference and caregivers’ burden in early‐onset Alzheimer's disease

Abstract: Background: Caregiver burden is the stress experienced as a result of caregiving. Despite the increasing number of Alzheimer's disease (AD) patients who are cared for at home, little has been published about the caregiver burden pertaining to caregivers of early-onset AD patients. The objective of this study was to examine the difference between the genders with respect to the careburden of early-onset AD caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 12 publications
2
19
0
3
Order By: Relevance
“…(). This may reflect the tendency of females to desire harmony in family relationships (Takano & Arai ). In turn, females are likely to regard providing care to ill family members as natural responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…(). This may reflect the tendency of females to desire harmony in family relationships (Takano & Arai ). In turn, females are likely to regard providing care to ill family members as natural responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions should target caregivers of behaviorally disturbed patients, as well as caregivers who report poor physical health, to reduce the negative psychological impact of caregiving. In Japan, Takano and Arai 9 reported that female caregivers are more likely to experience care burden than male caregivers, and showed the importance of mental health support for female caregivers. Hirakawa et al 10 carried out a study which gave a better understanding of the Japanese male caregiver burden in home care.…”
Section: Discussionmentioning
confidence: 99%
“…Women provide care for a longer period of time than men (Shriver & Alzheimer's Association, 2010) and spend more hours per day undertaking caregiving tasks (Kim et al, 2011). There appears to be a consensus that female caregivers experience higher levels of burden, stress and depressive symptoms than male caregivers, with similar outcomes being reported across different countries and settings (Iavarone et al, 2014;Papastavrou et al, 2009;Davies et al, 2012;Akpınar et al, 2011;Prince et al, 2012;Takano & Arai, 2005;Stewart et al, 2014;Zhang et al, 2006;Pöysti et al, 2012;Välimäki et al, 2009), although there are some conflicting reports on this (Croog et al 2006). This is independent of their relationship to the care recipient and their characteristics, and care structures in place (Prince et al, 2012;Peel & Harding, 2014).…”
Section: Impact Of Caregivingmentioning
confidence: 99%